Sked, The Decline and Fall of the Habsburg Empire, 1815-1918 - Lowry, Bullitt (Teaching History: A Journal of Methods, 1991)
In a densely packed book, Alan Sked of the London School of Economics offers what he calls an extended essay on the decline of the Habsburg Empire in the nineteenth century. Sked, who has already published a number of specialized works on the Habsburg Empire, here tries to present an accessible study of the causes for its collapse. The basic question he is attacking, Sked says in his introduction, is to determine at what point the collapse became inevitable. He suggests, too, that the Austrian experience might help in solving problems emerging as Europe moves toward integration; looking at how the Habsburgs ruled a large number of quite different peoples, often peoples hostile to each other, can guide today's politicians.